2011
DOI: 10.1007/s11803-011-0044-6
|View full text |Cite
|
Sign up to set email alerts
|

Strength failure of spatial reticulated structures under multi-support excitation

Abstract: Under strong earthquakes, long-span spatial latticed structures may collapse due to dynamic instability or strength failure. The elasto-plastic dynamic behaviors of three spatial latticed structures, including two double-layer cylindrical shells and one spherical shell constructed for the 2008 Olympic Games in Beijing, were quantitatively examined under multi-support excitation (MSE) and uniform support excitation (USE). In the numerical analyses, several important parameters were investigated such as the peak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…According to the LPGA changing to the cubic curve model is the best model among several different models of curve estimation with a very small variance 0.1122. Referring to Equation (11), the relationship between the lower bound collapse loads and rise to span ratios could be given by: where RSR ∈ [0.1, 0.5] is the rise to span ratio.…”
Section: Relationship Between Lower Bound Collapse Loads and Rise To mentioning
confidence: 99%
See 2 more Smart Citations
“…According to the LPGA changing to the cubic curve model is the best model among several different models of curve estimation with a very small variance 0.1122. Referring to Equation (11), the relationship between the lower bound collapse loads and rise to span ratios could be given by: where RSR ∈ [0.1, 0.5] is the rise to span ratio.…”
Section: Relationship Between Lower Bound Collapse Loads and Rise To mentioning
confidence: 99%
“…Referring to Equation (11), the relationship between lower bound collapse loads and rise to span ratios could be given by:…”
Section: Table 10mentioning
confidence: 99%
See 1 more Smart Citation
“…12 The coherence models are often considered in the estimation of the seismic responses of structures or structural systems with multiple supports. [13][14][15][16][17][18][19] In these studies, simulated ground motion records are used since the available historical records are insufficient for selecting the records matching inter-support distances of a structure, desired seismic magnitude (or intensity) and site to seismic source distance. For example, ground motion records are simulated for a target power spectral density (PSD) function and a predefined coherence function for analysing the response of the transmission line towers in Yang et al, 20 for multi-span bridges in Soyluk and Sicacik, 16 and for spatial reticulated structures in previous studies.…”
Section: Introductionmentioning
confidence: 99%
“…For example, ground motion records are simulated for a target power spectral density (PSD) function and a predefined coherence function for analysing the response of the transmission line towers in Yang et al, 20 for multi-span bridges in Soyluk and Sicacik, 16 and for spatial reticulated structures in previous studies. 17,18,21,22 The flexibility of substructures can also influence the responses of latticed shells. [23][24][25] The records simulated and used in these studies cannot reproduce the observed spatial correlation of ground motion measures or the Fourier amplitude spectrum (FAS), and are not directly linked to scenario events that are often characterized by the combination of the earthquake magnitude and site to seismic source distance.…”
Section: Introductionmentioning
confidence: 99%